Das hebräische Partizip in den Texten aus der judäischen Wüste - Geiger, Gregor, 1969- (Studies on the Texts of the Desert of Judah, 2012)
The function of the participle within the Hebrew tense system has considerably changed between biblical and postbiblical Hebrew. This investigation studies the participle in the Hebrew manuscripts from the Judaean Desert, its formation, its usage, and its meaning, compared with those in other Hebrew traditions and dialects, especially the language of the Hebrew Bible. The biblical Hebrew tense system continues to be used in the Scrolls, while there is a clear difference between the tense system of the Scrolls and that of mishnaic Hebrew. This fact allows us to draw conclusions in the field of language studies; but it also provides us with a piece of the puzzle in our understanding of the sociology and religion of the Qumran community. Die Funktion des Partizips innerhalb des hebräischen Tempussystems wandelte sich erheblich zwischen biblischem und nach-biblischem Hebräisch. Diese Studie untersucht das Partizip in den hebräischen Handschriften aus der judäischen Wüste, seine Bildung, seine Verwendung und seine Bedeutung, im Vergleich mit anderen hebräischen Traditionen und Dialekten, vor allem der Sprache der hebräischen Bibel. Das biblisch-hebräische Tempussystem findet seine Fortsetzung in diesen Handschriften, während es einen klaren Unterschied zwischen deren Tempussystem und dem des mischnischen Hebräisch gibt. Diese Tatsache erlaubt Rückschlüsse im Bereich der Sprachwissenschaft, sie liefert aber auch einen Mosaikstein in unserem Verständnis von Gesellschaft und Religion der Qumran-Gemeinschaft.